(untitled) (Muitas Vozes, 2021)
We propose a critical comparative analysis between the concept of Metaphorical Effect as defined by Pêcheux in 1969 and some concepts in the works of Saussure: Course in General Linguistics and Writings in General Linguistics. The publication of Course in General Linguistics in 1916 caused a widespread rupture in the methods and epistemology of Human Sciences. Not a mere influence, Saussurean linguistics brought a paradigmatic rupture that paved the way for the development of many theories. French Discourse Analysis, proposed by Michel Pêcheux, arises as an in-between area of Saussurean linguistics, Historical Materialism, and Psychoanalysis. Pêcheux’s Automatic Discourse Analysis is the groundwork of this area and defines its fundamental theoretical framework, where he developed the Metaphorical Effect: a mechanism through which it is possible to replace words and yet maintain the discourse’s semantic effects. Evoking the concept of Language State as an anchoring point, we could look into Syntagmatic and Associative Relations functioning alongside the Metaphorical Effect, thus, establishing conditions to approach discursively the evolution of language in relation with the commitments of the mind and the Analogy. With a renewed interest of the academic community in the ADA69, we aim to bring for these analysts a deeper understanding of the Metaphorical Effect through reexamining key concepts in Saussurean Linguistics.